2007
DOI: 10.1149/1.2731205
|View full text |Cite
|
Sign up to set email alerts
|

Etching of Germanium in Hydrogenperoxide Solutions

Abstract: In this paper, the etching behaviour of germanium in hydrogen peroxide solutions is described. Electrochemical experiments showed that the etching process is most probably purely chemical. The etch rate was found to depend upon the H2O2 concentration, the pH value, the amount of KCl in the solution and , in some cases, upon the rotation rate. Based on all of these findings, possible etching mechanisms for Ge in H2O2 are discussed on a molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…The above displacement reaction competes with surface hydroxylation and consequently releases Ge atoms Ge (aqua)chloro complexes. 36,45 The presence of surface chlorides, rather than the protons, accelerates the desorption/dissolution of oxidation products as supported by the XPS results (Figs. 3-4).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The above displacement reaction competes with surface hydroxylation and consequently releases Ge atoms Ge (aqua)chloro complexes. 36,45 The presence of surface chlorides, rather than the protons, accelerates the desorption/dissolution of oxidation products as supported by the XPS results (Figs. 3-4).…”
Section: Resultsmentioning
confidence: 64%
“…Later, an electrochemical study by Gerischer and co-workers 38 suggested a purely chemical mechanism for the acidic H 2 O 2 etchant, which was also supported by the work of Huygens via profilometry and electrochemical experiments for electrolytes of various pH. 36 Furthermore, Sioncke and co-workers provided extensive etch rate data for a wide range of acidic and alkaline solutions. 29 Numerous wet passivation methods have also been investigated that were based on halogenic acids such as HF, 39,40 HBr, 41 HI 42 and HCl.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…With the continuous oxidation from H 2 O 2 and oxide removal from acid, Ge could be thinned down. It should be noted that an anion like Cl – may play a more important role in the etching process than proton concentration. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure b,c shows the Ge wet etching process, both in the middle of the etching and after, respectively. The reaction of the H 2 O 2 solution with Ge in order to dissolve it is well known and is given in eqs and …”
Section: Resultsmentioning
confidence: 99%